Fussing and fuming over Fannie and Freddie: how much smoke, how much fire? - W. Scott Frame; Lawrence J. White (Federal Reserve Bank of Atlanta, 2004)
The roles of Fannie Mae and Freddie Mac have become increasingly controversial in the modern world of residential mortgage finance. The authors describe the special features of these two companies and their roles in the mortgage markets and then discuss the controversies that surround the companies and offer recommendations for improvements in public policy.
Keywords: 330; Hypothekenbank; Hypothek; Verbriefung; Subvention; USA